Levi Wells Ostrander papers - Ostrander, Levi Wells, 1841-1921.
Chiefly letters of Ostrander to his parents, Jared Fordham Ostrander and Rowena Wells Ostrander, documenting his Civil War service with the 29th Wisconsin Infantry Regiment, U.S. Army, in the Western theater. Subjects include camp life and troop movements, encounters with African Americans, voting in the field and election returns, and the siege and fall of Vicksburg, Miss., in 1863. lncludes transcripts of the letters, two Grand Army of the Republic medals, photocopies of family photographs, and other printed matter relating to the Ostrander family.
Union Army soldier.
Collection material in English.
Keywords: Ostrander, Jared Fordham, -- 1805-1874 -- Correspondence; Ostrander, Rowena Wells, -- 1802-1889 -- Correspondence; Ostrander family; United States. -- Army -- Military life; United States. -- Army. -- Wisconsin Infantry Regiment, 29th (1862-1865); Grand Army of the Republic -- Medals; Mississippi -- History -- Civil War, 1861-1865.; United States -- History -- Civil War, 1861-1865.; United States -- History -- Civil War, 1861-1865 -- African Americans; United States -- Politics and government -- 1861-1865.; Vicksburg (Miss.) -- History -- Civil War, 1861-1865.; Vicksburg (Miss.) -- History -- Siege, 1863.; Wisconsin -- History -- Civil War, 1861-1865.; Soldiers